Numerical investigation on the mechanism of the effects of plate vibration on mixing and combustion of transverse hydrogen injection. (13th December 2018) - Ye, Kun; Ye, Zhengyin; Li, Chunna; Wu, Jie
Abstract: This study numerically investigates the effects of plate vibration and deformation on the combustion performance, the shock wave structure, the mixing characteristics and the flame structure for transverse hydrogen injection. The finite-rate method is used to simulate combustion. Results show that plate vibration causes the combustion performance to oscillate both temporally and spatially, while plate deformation can only change the static characteristics of the flow. Plate vibration and deformation increase the intensity and number of shock wave reflections in different ways. In addition, both plate vibration and deformation increase the momentum flux ratio and the jet penetration depth, which enhances mixing. Finally, plate vibration widens the flame and moves it upward to a greater extent than plate deformation. Highlights: Mechanism for the effects of plate vibration on mixing and combustion is analyzed. Plate vibration and deformation change shock wave structure in different way. Plate vibration and deformation increase mixing characteristics. Plate vibration and deformation widens the flame and moves it upward.